Targeting the Immune System with Plant Lectins to Combat Microbial Infections - Jandú, Jannyson J. B.; Moraes Neto, Roberval N.; Zagmignan, Adrielle; de Sousa, Eduardo M.; Brelaz-de-Castro, Maria C. A.; dos Santos Correia, Maria T.; da Silva, Luís C. N. (Frontiers in Pharmacology, 2017)
The arsenal of drugs available to treat infections caused by eukaryotic and prokaryotic microbes has been declining exponentially due antimicrobial resistance phenomenon, leading to an urgent need to develop new therapeutic strategies. Host-directed immunotherapy has been reported as an attractive option to treat microbial infections. It consists in the improvement of host defenses by increasing the expression of inflammatory mediators and/or controlling of inflammation-induced tissue injury. Although the in vitro antimicrobial and immunomodulatory activities of lectins have been extensively demonstrated, few studies have evaluated their in vivo effects on experimental models of infections. In fact, these in vivo studies used immunomodulatory lectins to combat microbial infections. This review aims to highlight the experimental use of immunomodulatory plant lectins to improve the host immune response against microbial infections. Lectins have been used both prophylactically and therapeutically resulting in the increased survival of mice under microbial challenge. Other studies successfully demonstrated that lectins could be used in combination with parasite antigens in order to induce a more efficient immunization. Therefore, these plant lectins represent new candidates for management of microbial infections. Furthermore, immunotherapeutic studies have improved our knowledge about the mechanisms involved in host-pathogen interactions, and may also help in the discovery of new drug targets.